Setting the Stage for Progress: Introducing PRIEN Journal to the World - Faramarzi, Salar (Psychological Research in Individuals with Exceptional Needs, 2024)
The establishment of the Psychological Research in Individuals with Exceptional Needs (PRIEN) Journal marks a significant milestone in the field of psychology. This pioneering international academic journal is dedicated to addressing the multifaceted psychological needs of individuals with exceptionalities. Our mission is to promote understanding, support, and advancement for those with unique psychological needs, ranging from developmental and emotional challenges to cognitive exceptionalities and giftedness. As we introduce PRIEN Journal to the world, we aim to set the stage for meaningful progress in this crucial field. The landscape of psychological research is vast, yet there remains a critical need for focused studies on individuals with exceptional needs. The PRIEN Journal addresses this gap by offering a platform for high-quality original research, comprehensive reviews, thought-provoking editorials, and insightful communications. This focus ensures that our content is relevant and beneficial to both practitioners and scholars who work with this diverse population. Our journal aims to highlight such impactful studies and bring them to the forefront of academic and clinical practice. As we launch the PRIEN Journal, we invite researchers, practitioners, and scholars to contribute their work and join us in advancing the understanding and support of individuals with exceptional needs. Together, we can set the stage for progress, driving forward research and practice that will make a meaningful difference in the lives of those we serve.